Technology and the public interest / Haochen Sun. - Sun, Haochen (Cambridge University Press, 2022)
In this groundbreaking work, Haochen Sun analyzes the ethical crisis unfolding at the intersection of technology and the public interest. He examines technology companies' growing power and their increasing disregard for the public good. To tackle this asymmetry of power and responsibility, he argues that we must reexamine the nature and scope of the right to technology and dynamically protect it as a human right under international law, a collective right under domestic civil rights law, and potentially a fundamental right under domestic constitutional law. He also develops the concept of fundamental corporate responsibility requiring technology companies to compensate users for their contributions, assume an active role responsibility in upholding the public interest, and counter injustices caused by technological developments.